The importance of Forbidden Islam in Spiritual Growth, Problems And Solutions - Turgunbaev Tohirjon Abdugafurovich (International Journal on Human-Computing Studies, 2021)
The article presents a brief history of the origin of world religions, the spiritual and educational significance of religion in the context of globalization, as well as provides information on problems and solutions.